Strategies of Fostering Writing Skills to Improve EFL Learners’ Writing Fluency in Erbil Secondary Schools - Eiram Amjed Khidhir; Nada Jabbar Abbas (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The development of writing fluency is a fundamental element of writing skills and learning a language. The current study investigates five selected writing strategies, as repeated writing, timed writing, story circle, diary writing, and peer editing strategy effects on writing fluency and EFL learners’ production of meaningful texts. It studies the perceptions of 153 EFL secondary school teachers of the effect of five selected writing strategies on students’ writing fluency in Erbil city of Kurdistan region in Iraq. The data results indicated the positive effects of the writing strategies in increasing writing fluency. The effect of the writing strategies on improving writing fluency is compared by gender (t-test). This work also explores the effect of the selected five writing strategies on students’ self-efficacy. Recommendations for further researches are presented.